Liver Fibrosis in HIV Patients Receiving a Modern cART: Which Factors Play a Role?. Issue 50 (December 2015) - Mohr, Raphael; Schierwagen, Robert; Schwarze-Zander, Carolynne; Boesecke, Christoph; Wasmuth, Jan-Christian; Trebicka, Jonel; Rockstroh, Jürgen Kurt
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Liver-related death in human immunodeficiency virus (HIV)-infected individuals is about 10 times higher compared with the general population, and the prevalence of significant liver fibrosis in those with HIV approaches 15%. The present study aimed to assess risk factors for development of hepatic fibrosis in HIV patients receiving a modern combination anti-retroviral therapy (cART). This cross-sectional prospective study included 432 HIV patients, of which 68 (16%) patients were anti-hepatitis C virus (HCV) positive and 23 (5%) were HBsAg positive. Health trajectory including clinical characteristics and liver fibrosis stage assessed by transient elastography were collected at inclusion. Liver stiffness values >7.1 kPa were considered as significant fibrosis, while values >12.5 kPa were defined as severe fibrosis. Logistic regression and Cox regression uni- and multivariate analyses were performed to identify independent factors associated with liver fibrosis. Significant liver fibrosis was detected in 10% of HIV mono-infected, in 37% of HCV co-infected patients, and in 18% of hepatitis B virus co-infected patients. The presence of diabetes mellitus (odds ratio [OR] = 4.6) and FIB4 score (OR = 2.4) were independently associated with presence of significant fibrosis in the whole cohort. Similarly, diabetes mellitus (OR = 5.4), adiposity (OR = 4.6), and the FIB4 score (OR = 3.3) were independently associated with significant fibrosis in HIV mono-infected patients. Importantly, cumulative cART duration protected, whereas persistent HIV viral replication promoted the development of significant liver fibrosis along the duration of HIV infection. Our findings strongly indicate that besides known risk factors like metabolic disorders, HIV may also have a direct effect on fibrogenesis. Successful cART leading to complete suppression of HIV replication might protect from development of liver fibrosis.